Peer-to-peer (P2P) accommodation in the sharing economy: a review. Issue 19 (2nd October 2022) - Kuhzady, Salar; Seyfi, Siamak; Béal, Luc
ABSTRACT: Accommodation has been viewed as the largest and most important sector in the tourism industry. This paper provides a systematic review of 371 papers identified in SCOPUS and WOS databases between 2000 and 2019 on P2P accommodation in the sharing economy. Research on P2P accommodation is experiencing high growth, with Airbnb a major focus for tourism scholars. The provision of authentic experiences, environmental concerns, and socialization are important themes in P2P accommodation research, with trust and negative attitudes of established businesses and government regarded as the main barriers of P2P development. Common strategies to respond P2P accommodation platforms are also identified.